The role of the brachialis muscle in elbow stability with collateral ligament injury: A biomechanical investigation. (October 2021) - Ott, Nadine; Harland, Arne; Knevels, Michael; Hackl, Michael; Leschinger, Tim; Lanzerath, Fabian; Scaal, Martin; Wegmann, Kilian; Müller, Lars Peter
Abstract: Background: The brachialis muscle lies in close anatomic relation to the anterior capsule of the elbow joint. The contribution of the brachialis muscle to elbow stability has not yet been fully investigated. Therefore, the aim of this biomechanical in-vitro study was to analyze its influence on joint stability. Methods: Nine fresh frozen cadaveric elbows were evaluated for stability against valgus and varus/posterolateral rotatory forces. Brachialis loading was measured indirectly using strain gauges. Three distinct scenarios were analyzed: A) with intact lateral ulnar and ulnar collateral ligaments B) with a ruptured lateral ulnar collateral ligament C) with ruptured lateral ulnar and ulnar collateral ligaments. Findings: In all scenarios, an increased strain was observed under posterolateral rotatory/varus forces. The maximum measured strain occurred with elbow flexion of 30° and pronation of the forearm. The strain was significantly higher with dual-ligament rupture (mean - 210.5 μm/m; min. 97.8 μm/m; max. -310 μm/m; SD 107.8 μm/m; p = .034) compared to intact ligaments (mean − 106.9 μm/m; min. -32.51 μm/m, max. -287 μm/m; SD 100.2 μm/m) and single-ligament rupture (mean – 109.5 μm/m; min. - 96.7 μm/m; max - 130.4 μm/m; SD 18.2). Interpretation: A strain of the brachialis muscle was observed under varus/posterolateral rotatory forces with a pronated forearm and the strain increased significantly in the event of a dual-ligament rupture. This suggests that the brachialis muscle may influence varus/posterolateral rotatory stability of the elbow. Hence, a concomitant tear of the brachialis muscle might result in pronounced instability following simple elbow dislocation. Level of evidence: Basic Science Study, Biomechanics. Highlights: The study analyzed the strain of the brachialis muscle by using strain gauges. A strain of the brachialis muscle was observed under varus forces with a pronated forearm. The strain increased significantly in case of a ruptured ulnar and lateral collateral ligament. A concomitant tear of the brachialis muscle may result in pronounced instability.